The feasibility of diagnosing sprained ankle via 3D MRI reconstructing three-dimensional model of anterior talofibular ligament - He, Lei; Dai, Meng; Xu, Yan; Ouyang, Liu; Duan, Deyu; Huang, Zhaogang; Xiang, Chenghao (Frontiers in Sports and Active Living, 2024)
The anterior talofibular ligament (ATFL) is the most vulnerable ligament in ankle sprains. Most patients recover after this injury with conservative treatment, while 20% to 40% progress to chronic ankle instability that requires surgical stabilization.Conventional MRI does not provide a comprehensive image of the ATFL. We aimed to evaluate the feasibility of using 3D MRI to facilitate the understanding of ATFL injuries and the operative planning. A total of 21 healthy asymptomatic volunteers with 30 normally functioning ankles and 13 patients with 18 sprained ankles were studied. MRI scans were divided into two groups: Group 1 (normal ankle) and Group 2 (injured ankle). The data of all 48 cases were exported to Mimics and reconstructed into 3D models. The image quality of all 3D models was evaluated using a 5-point subjective scoring system. The length, width, and thickness of the ATFL were measured in the 3D model in Mimics and compared to the 3D MPR image data. The image quality score was 4.57±0.32. There was no statistically significant difference between the 3D model and the 3D MPR image of ATFL measurements in both groups (P＞0.05). We concluded that 3D MRI can be used to reconstruct a 3D model of the ATFL for accurate measurements of the ATFL anatomical structure, which holds potential to improve preoperative planning and intraoperative navigation for young sports medicine doctor, facilitate diagnosis of ATFL injuries and make the decision about the operative method.